The characteristics and experience of community food program users in arctic Canada: a case study from Iqaluit, Nunavut - Ford, James (BioMed Central, 2012)
BACKGROUND: Community food programs (CFPs), including soup kitchens and food banks, are a recent development in larger settlements in the Canadian Arctic. Our understanding of utilization of these programs is limited as food systems research has not studied the marginalised and transient populations using CFPs, constraining service planning for some of the most vulnerable community members. This paper reports on a baseline study conducted with users of CFPs in Iqaluit, Nunavut, to identify and characterize utilization and document their food security experience. METHODS: Open ended interviews and a fixed-choice survey on a census (n = 94) were conducted with of users of the food bank, soup kitchen, and friendship centre over a 1 month period, along with key informant interviews. RESULTS: Users of CFPs are more likely to be Inuit, be unemployed, and have not completed high school compared to the general Iqaluit population, while also reporting high dependence on social assistance, low household income, and an absence of hunters in the household. The majority report using CFPs for over a year and on a regular basis. CONCLUSIONS: The inability of users to obtain sufficient food must be understood in the context of socio-economic transformations that have affected Inuit society over the last half century as former semi-nomadic hunting groups were resettled into permanent settlements. The resulting livelihood changes profoundly affected how food is produced, processed, distributed, and consumed, and the socio-cultural relationships surrounding such activities. Consequences have included the rising importance of material resources for food access, the weakening of social safety mechanisms through which more vulnerable community members would have traditionally been supported, and acculturative stress. Addressing these broader challenges is essential for food policy, yet CFPs also have an essential role in providing for those who would otherwise have limited food access.